2018
DOI: 10.4034/pboci.2018.181.81
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Dental and Family Living Condition Approach for Planning Dental Care: A Cross-sectional Study among Indonesian Students

Abstract: Objective: To know the planning of dental care with a socio-dental approach. Material and Methods: Cross-sectional study has been conducted on Baubau Junior High School students, Southeast Sulawesi. The sample consisted of 209 subjects randomly selected. The social approach is known for filling out questionnaires with Family Development Index (FDI), Quality of life with OHRQoL-index using Child-OIDP (specific and generic). Family data were: family income, housing conditions (material used in the construction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…This could be due to government regulations that limit the types of dental health services that can be carried out and because of increased public fear of COVID-19, so people prefer to stay at home and only a few go-to dental care clinics [25]. This study showed that 27.6% of respondents chose not to go to the clinic/dentist's practice because of the types of dental and oral health services that were restricted during the COVID-19 pandemic and 26.0% of subjects were afraid of contracting [26], while the need for dental health care based on the results of previous studies as much as 84.2% and an impact on quality of life as much as 72.1% [27]. The results of the study before obtaining the impact of dental health problems especially dental caries on the quality of life of children aged 8-10 years by 68.0% [28].…”
Section: Resultsmentioning
confidence: 86%
“…This could be due to government regulations that limit the types of dental health services that can be carried out and because of increased public fear of COVID-19, so people prefer to stay at home and only a few go-to dental care clinics [25]. This study showed that 27.6% of respondents chose not to go to the clinic/dentist's practice because of the types of dental and oral health services that were restricted during the COVID-19 pandemic and 26.0% of subjects were afraid of contracting [26], while the need for dental health care based on the results of previous studies as much as 84.2% and an impact on quality of life as much as 72.1% [27]. The results of the study before obtaining the impact of dental health problems especially dental caries on the quality of life of children aged 8-10 years by 68.0% [28].…”
Section: Resultsmentioning
confidence: 86%
“…If grouped based on Family Development Index (FDI), including people with the very severe category. The results of research conducted in Bau-Bau Indonesia were obtained equal to 83.3%, so they really needed to be given special attention in maintaining their health [22].…”
Section: Discussionmentioning
confidence: 99%